Linguistic attitudes of university students towards Quechua and Spanish languages - Roldán Rosales, Óscar Esteban (2021)
This descriptive correlational study aimed to analyze the linguistic attitudes shown by the students of the National University “Santiago Antúnez de Mayolo” towards Quechua and Spanish, for which the survey was used as a data collection technique, the was applied to a sample of 150 students, who had to answer 12 questions based on the research variable. The results indicated that the students have different opinions about the Quechua and Spanish languages, although they show a higher positive assessment of the Spanish language. Likewise, they assign different degrees of use, although Spanish is the most preferred language. Therefore, it is concluded that students grant favorable attitudes towards Quechua and Spanish. Thus, with regard to attitudes towards Quechua, positive evaluations are given in the sense that this language provides them with better opportunities for family and social interrelation, job opportunities and eventually economic progress, while Spanish valuations prevail in reason for sociocultural, economic and academic purposes. In addition, the sample investigated showed a high preference for the use of the Spanish language since this language is the one that is predominantly used in daily communications, and they also have a high degree of awareness and sensitivity towards the cultural and linguistic identity of Quechua.